Fabrication and high-temperature mechanical properties of 2.5DSi3N4f/BN fiber-reinforced ceramic matrix composite. (15th February 2016) - Zou, Chunrong; Li, Bin; Wang, Siqing; Zhang, Changrui; Song, Yangxi; Xie, Zhengfang; Shao, Changwei
Abstract: Wave-transparent components to protect radar equipment from aerodynamic load and heat requires highly mechanical reliability at high temperatures. This study reports the microstructure, high-temperature mechanical properties and oxidation behavior of a new 2.5DSi3 N4f /BN wave-transparent composite prepared by a borazine infiltration and pyrolysis route. The obtained composite had a relative density of 91.1% and the derived BN matrix was turbostratic in microstructure with a low interlayer spacing of 3.44 Ǻ. The bending strength of the composite at room temperature was 132.6 MPa, which decreased to 120.8 MPa upon in-situ testing at 1000 °C in air, and further declined to 101.2 and 73.4 MPa when tested at 1200 and 1300 °C without evidence for brittle fracture. The strength degradation was related to the oxidation of the composite at high temperatures. The oxidation of BN matrix was the predominant oxidation of the composite below 1200 °C while liquid B2 O3 became less protective as the temperature increased. A more oxygen-resistant viscous SiO2 -rich glass was formed beyond 1200 °C due to the oxidation of the reinforcing fibers, which enlarged the temperature range of passive oxidation up to 1400 °C and prevented the composite from excessive oxidation. Graphical abstract: Highlights: A dense boron nitride matrix composite with braided silicon fibers was fabricated by borazine infiltration and pyrolysis method. The precursor derived boron nitride matrix was turbostratic in microstructure with a low interlayer spacing of 3.44 Ǻ. A thin layer of highly ordered boron nitride matrix was observed to align parallel to the fiber surface. The composite retained a desirable in-situ bending strength of 73.4 MPa after held at 1300 °C for 30 min. The presence of viscous SiO2 -rich glass above 1200 °C led to the passive oxidation of the composite.